SIRT3 regulates cellular iron metabolism and cancer growth by repressing iron regulatory protein 1 - Jeong, Seung Min (Oncogene, 2014)
Iron metabolism is essential for many cellular processes including oxygen transport, respiration and DNA synthesis, and many cancer cells exhibit dysregulation in iron metabolism. Maintenance of cellular iron homeostasis is regulated by iron regulatory proteins (IRPs), which control the expression of iron-related genes by binding iron-responsive elements (IREs) of target mRNAs. Here, we report that mitochondrial SIRT3 regulates cellular iron metabolism by modulating IRP1 activity. SIRT3 loss increases reactive oxygen species production, leading to elevated IRP1 binding to IREs. As a consequence, IRP1 target genes, such as the transferrin receptor (TfR1), a membrane-associated glycoprotein critical for iron uptake and cell proliferation, are controlled by SIRT3. Importantly, SIRT3 deficiency results in a defect in cellular iron homeostasis. SIRT3 null cells contain high levels of iron and lose iron-dependent TfR1 regulation. Moreover, SIRT3 null mice exhibit higher levels of iron and TfR1 expression in the pancreas. We found that the regulation of iron uptake and TfR1 expression contribute to the tumor suppressive activity of SIRT3. Indeed, SIRT3 expression is negatively correlated with TfR1 expression in human pancreatic cancers. SIRT3 overexpression decreases TfR1 expression by inhibiting IRP1 and represses proliferation in pancreatic cancer cells. Our data uncover a novel role of SIRT3 in cellular iron metabolism through IRP1 regulation, and suggest that SIRT3 functions as a tumor suppressor, in part, by modulating cellular iron metabolism.